Programmed Photodegradation of Polymeric/Oligomeric Materials Derived from Renewable Bioresources1. (12th November 2014) - Rajendran, Saravanakumar; Raghunathan, Ramya; Hevus, Ivan; Krishnan, Retheesh; Ugrinov, Angel; Sibi, Mukund P.; Webster, Dean C.; Sivaguru, Jayaraman
Abstract Renewable polymeric materials derived from biomass with built‐in phototriggers were synthesized and evaluated for degradation under irradiation of UV light. Complete decomposition of the polymeric materials was observed with recovery of the monomer that was used to resynthesize the polymers.